Understanding Partnerships With Patients/Clients in a Team Context Through Verbatim Theater - Sylvia Langlois; Jessica Teicher; Amy Derochie; Vibhuti Jethava; Scott Molley; Shara Nauth (Association of American Medical Colleges, 2017)
Introduction Patient partnership has come to the forefront in health care practice and education, influencing professional programs and interprofessional education curricula. While students conceptually understand the idea of partnering with the patient, the practice of doing so is more challenging. Innovative ways to teach this health care approach may be effective in enabling students to apply their learning and promote enhanced patient partnerships. This resource provides an arts-based approach for exploring notions of partnerships with patients in a team context with interprofessional collaboration. Method This 2-hour resource features a verbatim reader's theater script and accompanying discussion questions for a small-group reading and debrief activity. The voice of individuals with lived experience is elevated to enhance student learning and connection to the topic. Quotations were taken from interviews with individuals who had experience with the health care system and from health care providers. Results The script and accompanying small-group discussion questions have been used in the interprofessional education curriculum with approximately 1,100 health profession students. Student response has been positive, indicating a new appreciation for thinking about partnering with patients. Discussion Although the script has been used in the context of interprofessional education, it has the potential to be used as part of uniprofessional teaching and in practice environments, since understanding the nature of partnerships between practitioners and patients transcends all settings.